Basis and effects of ion migration on photovoltaic performance of perovskite solar cells. (11th November 2020) - Zhou, Wenke; Gu, Juan; Yang, Zhiqian; Wang, Mingyang; Zhao, Qing
Abstract: Halide perovskite materials, which are emerging as some of the most promising candidates for photovoltaics, have been widely studied and have been certified as demonstrating a comparable efficiency to single-crystal silicon solar cells. However, their low stability poses a challenge for commercialization. External impediments, like moisture, heat, and UV light, can be addressed by strict encapsulation; nevertheless, ion migration remains. The migrated ions will bring in a growing number of charged defects and phase segregation to bulk perovskite; they will cause interfacial band doping and degradation of the carrier transport layer, which will greatly hinder carrier transportation. Those effects are the origins of perovskite intrinsic instability. Thus, a thorough understanding of the operational mechanism of ion migration is urgent for the fabrication of perovskite solar cells (PSCs) with improved stability. Here, we systemically summarize the factors governing ion migration in perovskite film and the associated impact on the performance of PSCs. Light illumination, organic cations, grain boundaries, residue lattice strain and moisture have been found to make ion migration easier. Strategies developed to suppress the ion migration are also interspersed in each section.